Massonia bakeriana (Asparagaceae, Scilloideae), a new pustulate species from the Northern Cape Province (South Africa) - Pinter, Michael; Martínez Azorín, Mario; Crespo, Manuel B.; Wetschnig, Wolfgang (Phytotaxa, 2015)
As part of a taxonomic revision of the genus Massonia, a new species, M. bakeriana, is here described from the Northern Cape (South Africa). This species is at first sight similar to M. echinata and M. mimetica, but it differs in vegetative, floral, and molecular characters as well as by its ecology and distribution. A complete morphological description of the new species and data on biology, habitat, and distribution are presented.